Safety profile of subacute oral administration of ethanolic extract of Gracilaria manilaensis Yamamoto & Trono - Nyiew, Ke-Ying *; Wong, Kah Hui; Lim, Lee Wei; Phang, Siew Moi; Shyamala, Ratnayeke; Yow, Yoon Yen * (Springer, 2024)
Gracilaria manilaensis is a red seaweed found in some regions of Peninsula Malaysia. In vitro studies have demonstrated that G. manilaensis has neuritogenic, neuroprotective, anticancer, antioxidant, and antimicrobial properties, suggesting that it could be developed into health supplement. However, the eﬀects of oral consumption of G. manilaensis have not yet been evaluated in vivo. The present study evaluated the safety of sub-acute oral consumption of G. manilaensis ethanolic extract. 10, 50, 100, 250, and 500 mg kg-1 G. manilaensis ethanolic extracts and distilled water (control) were administered to adult female Sprague-Dawley rats (n=3 per group) by oral gavage for 28 days. Our results showed that the G. manilaensis ethanolic extract did not induce abnormal behaviour, body weight changes, or aﬀect the mortality rate between treatment and control groups. There were no abnormal haematological and biochemical ﬁndings, except that 500 mg kg-1 G. manilaensis ethanolic extract may aﬀect renal function, as urea levels and urea/creatinine ratio were lower when compared to other treatment groups. Gross necropsy did not reveal any abnormalities in the vital organs in all groups. There were no signiﬁcant diﬀerences (p > 0.05) in the percentage relative weight of organs between treatment and control groups. In conclusion, the ﬁndings showed that daily oral consumption of G. manilaensis ethanolic extracts at 250 mg kg-1 or lower for 28 days was safe. The ﬁndings from this study provide a basis for future studies to investigate the in vivo health promoting eﬀects of G. manilaensis.